2022
DOI: 10.31348/2021/32
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Thrombolytic Therapy for Acute Nonarteritic Central Retinal Artery Occlusion. A Review

Abstract: Central retinal artery occlusion (CRAO) is a form of acute ischemic stroke. It is a critical condition that often leads to severe visual loss or blindness and can be a harbinger of further cerebrovascular events. Due to the lack of scientific data, there are no effective evidence-based forms of therapy for this condition. None of the conservative therapies have proven effective. The results of some previously published studies suggest a benefit of intravenous thrombolytic therapy in the same regimen as in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…If the patient has had symptoms for over 4.5 h, the patient should be commenced on antiplatelet therapy and reviewed by the acute stroke unit for workup and secondary prevention" [30]. Yet another review by Janská et al concluded, "It seems that the IVT efficacy and safety can be confirmed" [31]. Okonkwo et al made a case for neuroprotective strategies in patients with CRAO, and on the subject of IVT state "...intravenous (IV) thrombolysis (IV-tPA) in CRAO though controversial, could hold some promise for a category of patients who can have treatment early and perhaps suffer from incomplete arterial occlusion" [32].…”
Section: Literature Overviewmentioning
confidence: 99%
“…If the patient has had symptoms for over 4.5 h, the patient should be commenced on antiplatelet therapy and reviewed by the acute stroke unit for workup and secondary prevention" [30]. Yet another review by Janská et al concluded, "It seems that the IVT efficacy and safety can be confirmed" [31]. Okonkwo et al made a case for neuroprotective strategies in patients with CRAO, and on the subject of IVT state "...intravenous (IV) thrombolysis (IV-tPA) in CRAO though controversial, could hold some promise for a category of patients who can have treatment early and perhaps suffer from incomplete arterial occlusion" [32].…”
Section: Literature Overviewmentioning
confidence: 99%
“…This improvement is particularly notable for patients presenting with visual acuity of 20/40 or better. 5,[7][8][9] Critically, preventing significant vision loss has been accomplished with tPA treatment up to 12 hours after symptom onset. 1 However, it has been proposed that the clinically important time limit for inner retinal nonperfusion has been greatly overestimated since this value has mainly been determined by experimental studies that did not accurately model CRAO in nonhuman primates, 1 further adding to the uncertainty surrounding treatment for this condition.…”
mentioning
confidence: 99%